Accountability Management Effectiveness at PT. Dumas Tanjung Perak Shipyards in Surabaya - Dhiya Hanis Durrani (Journal of World Conference (JWC), 2019)
In shipyard companies, receivables are the main source of company revenue. Good control is needed so that it can run effectively and efficiently to avoid the risk of accounts that cannot be billed. But if the company cannot control it properly, the company will experience losses J12and even bankruptcy. This study aims to evaluate accounts receivable turnover so that it can be used as a tool to assess the effectiveness of company management. The analytical method used is quantitative descriptive analysis. The results of research obtained from the 2013-2017 financial statements, showed the average billing period (ACP) in 2014 = 43 days, 2015 = 42 days, 2016 = 58, and 2017 = 39 days. If it is associated with standard criteria, payment of receivables goes into in smooth criteria. This reflects that the management of the company's receivables is very good and optimal.